1991
DOI: 10.1007/bf00197154
|View full text |Cite
|
Sign up to set email alerts
|

An intronic duplication in the alanine: glyoxylate aminotransferase gene facilitates identification of mutations in compound heterozygote patients with primary hyperoxaluria type 1

Abstract: We report here the identification of a duplication within the first intron of the gene encoding human alanine:glyoxylate aminotransferase (AGT); this duplication is closely linked to two point mutations associated with peroxisome-to-mitochondrion mistargeting of AGT in primary hyperoxaluria type 1 (PH1) patients. Polymerase chain reaction amplification of regions of the AGT gene including the insertion site from individuals heterozygous for this duplication, produces allele-specific fragments of different size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…In addition to detection of c.33_34insC and other, less frequent changes that are located on exon 1, direct sequencing of this part of the coding region has the advantage of supplying P11L genotyping. Because of the strict association between P11L and IVS1 ϩ 74 bp documented in the past (9,11), the latter change has been used as a marker for the minor AGXT allele. The recent recognition of a breakage in this linkage, documented in an African population (33), underscores that IVS1 ϩ 74 bp may no longer be a suitable surrogate for P11L in certain populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to detection of c.33_34insC and other, less frequent changes that are located on exon 1, direct sequencing of this part of the coding region has the advantage of supplying P11L genotyping. Because of the strict association between P11L and IVS1 ϩ 74 bp documented in the past (9,11), the latter change has been used as a marker for the minor AGXT allele. The recent recognition of a breakage in this linkage, documented in an African population (33), underscores that IVS1 ϩ 74 bp may no longer be a suitable surrogate for P11L in certain populations.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to detection of the P11L and I340M polymor-phisms in patients with PH1 and mitochondrial AGT, Purdue et al (9) also identified a closely linked 74-bp duplication in intron 1 (IVS1 ϩ 74 bp). These three polymorphic variants (P11L, I340M, and IVS1 ϩ 74 bp) are now collectively referred to as the "minor" allele of AGXT.…”
mentioning
confidence: 99%
“…The primary, invariant, change in this allele is the presence of the c.32C4T change, which encodes leucine at codon 11 instead of the proline found in the major allele (AGT-Ma) . Additional sequence changes on the minor allele are the presence of a 74-bp imperfect duplication in intron 1 containing the two further substitutions c.166-100A4C and c.166-96T4A [Purdue et al, 1991a], a variable number of tandem repeats (VNTR) in intron 4 [Danpure et al, 1994b], and several other single nucleotide changes-c.165116A4G (Williams and Rumsby; Waterham; this work à ), c.264C4T [Danpure et al, 1994a], c.358113C4T ], and another missense change, p.Ile340Met (c.1020A4G) in exon 10 . The catalytic activity of the minor allele is significantly less than that of the major, ranging from $50 to 64% [Lumb and Danpure, 2000;Williams and Rumsby, 2007], with the difference entirely attributable to the leucine at codon 11 [Lumb and Danpure, 2000].…”
Section: Polymorphismsmentioning
confidence: 99%
“…Unfortunately, the liver-specific nature of AGT expression in humans precludes a comprehensive analysis of the relationship between the presence of the minor and major AGXT alleles and AGT activity in situ. Although the minor allele contains two amino acid substitutions (P11L and I340M), as well as a 74-base pair duplication in intron 1 (37) and a characteristic VNTR in intron 4 (38), it is only the P11L polymorphism that appears to have any affect on AGT function, including peroxisome-to-mitochondrion mistargeting, inhibition of dimerization, and decreased specific activity. In fact, as far as specific activity is concerned, it appears that the I340M polymorphism is able to, at least partially, normalize some of the consequences of the P11L polymorphism.…”
Section: Situ (Ie In Human Hepatocytes)mentioning
confidence: 99%